Dysphagia in the intensive care unit in Switzerland (DICE) – results of a national survey on the current standard of care (Swiss Medical Weekly, 2019)
INTRODUCTION Oropharyngeal dysphagia (OD) is often observed in critically ill patients. In most affected patients OD persists throughout hospital stay and negatively impacts on clinical outcomes. Here we systematically explore routine clinical practice standards for recognition/screening, diagnosis and treatment of OD in accredited Swiss ICUs. METHODS An online, 23-item questionnaire-based survey was performed to investigate current standards of care for OD in Switzerland (DICE). All (n = 49) accredited Swiss teaching hospitals providing specialist training for adult intensive care medicine were contacted. Senior intensivists were interviewed on how they would screen for, diagnose and treat OD in the ICU. RESULTS The total response rate was 75.5%, with information available on all tertiary care academic centres. 67.6% (25/37) of institutions stated that they have established standard operating procedures for OD using a mostly sequential diagnostic approach (86.5%, 32/37). In 75.7% (28/37) of institutions, OD confirmation is performed without the use of instrumental techniques such as flexible (or fibre-endoscopic) evaluation of swallowing (FEES). Presumed key risk factors for OD were admission for acute neurological illness, long-term mechanical ventilation, ICU-acquired weakness and pre-existing neurological disease. Reported presumed OD-related complications typically include aspiration-induced pneumonia, increased rates of both reintubation and tracheostomy and increased ICU readmission rates. CONCLUSIONS Many Swiss ICUs have established standard operating procedures, with most using sequential clinical approaches to assess ICU patients at risk of dysphagia. OD confirmation is mostly performed using non-instrumental techniques. In general, it appears that awareness of OD and ICU educational curricula can be further optimised. Trial registration number NCT 03487510